2023
DOI: 10.3389/feart.2023.1132093
|View full text |Cite
|
Sign up to set email alerts
|

An aeromagnetic denoising-decomposition-3D inversion approach for mineral exploration

Abstract: Reduction of aeromagnetic noise and extraction of mineralization-related residual anomalies are critical for aeromagnetic data processing in mineral exploration. This study introduced a multifractal singular value decomposition (MSVD) method to remove the noise and improved the bi-dimensional empirical mode decomposition (BEMD) algorithm to extract residual magnetic anomalies. It is shown that MSVD and improved BEMD could effectively reduce the noise and extract residual magnetic anomalies. Then, a wavenumber–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Pamukçu et al (2014) found that shallow Curie point depths (∼12 km), high heat flow values (∼80 mW/m 2), and thin crust in the north and northwest of the Bitlis-Zagros Suture Zone are associated with volcanic and geothermal areas. Researchers such as (Li et al, 2019;Abdullahi and Kumar, 2020;Ma et al, 2023;Yaro et al, 2023) also used this fractal method in determining the Curie depth to reveal the thermal structure.…”
Section: Resultsmentioning
confidence: 99%
“…Pamukçu et al (2014) found that shallow Curie point depths (∼12 km), high heat flow values (∼80 mW/m 2), and thin crust in the north and northwest of the Bitlis-Zagros Suture Zone are associated with volcanic and geothermal areas. Researchers such as (Li et al, 2019;Abdullahi and Kumar, 2020;Ma et al, 2023;Yaro et al, 2023) also used this fractal method in determining the Curie depth to reveal the thermal structure.…”
Section: Resultsmentioning
confidence: 99%